2006
DOI: 10.1007/s10532-005-3049-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Groundwater Contaminated with PAHs, Gasoline Hydrocarbons, and Methyl tert-butyl Ether in a Laboratory Biomass-Retaining Bioreactor

Abstract: In this study, we investigated the treatability of co-mingled groundwater contaminated with polycyclic aromatic hydrocarbons (PAHs), gasoline hydrocarbons, and methyl tert-butyl ether (MtBE) using an ex-situ aerobic biotreatment system. The PAHs of interest were naphthalene, methyl-naphthalene, acenaphthene, acenaphthylene, and carbazole. The gasoline hydrocarbons included benzene, toluene, ethyl benzene, and p-xylene (BTEX). Two porous pot reactors were operated for a period of 10 months under the same influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…5). This behavior was consistent with the fact that results published up to now have clearly demonstrated that the feasibility of BTX biodegradation through aerobic bioreactors could be considered as well established [23,24]. When the solid adsorbent was used with a low BTX loading (0.02 g/g), the residual pollutant concentration in the liquid was close to zero, as expected from Fig.…”
Section: Resultssupporting
confidence: 91%
“…5). This behavior was consistent with the fact that results published up to now have clearly demonstrated that the feasibility of BTX biodegradation through aerobic bioreactors could be considered as well established [23,24]. When the solid adsorbent was used with a low BTX loading (0.02 g/g), the residual pollutant concentration in the liquid was close to zero, as expected from Fig.…”
Section: Resultssupporting
confidence: 91%
“…Their limited biodegradability has been ascribed to their aromatic chemical structure, and to their low water solubility, which reduces their availability to degrading organisms, leading to persistence in the environment. This has fueled interest in PAH biodegradation, 16 which has been studied widely in singlephase aqueous systems, 17,18 liquid-liquid TPPB processes 19,20 and polymer-water TPPBs. 21 Although the latter have been shown to outperform single-phase aqueous biodegradations, polymers used in these demonstrations were selected by trial and error, rather than via the rational strategy developed in this work.…”
Section: Resultsmentioning
confidence: 99%
“…As such, remediating PAH-contaminated water is necessary to prevent exposure. Past wastewater, drinking water and ground water treatment schemes have shown that remediation can be accomplished in several ways [8][9][10][11][12]. Chemical oxidative processes are capable of degrading persistent and sorbed compounds and include treatments such as Fenton's reagent [13,14], modified Fenton's reagent [15], ozone [16,17], persulfate [15,18], or permanganate [15,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%